EFEKTIVITAS PENGELOLAAN ASET TETAP BARANG MILIK DAERAH PADA BADAN PENGELOLAAN KEUANGAN ASET DAERAH (BPKAD) KABUPATEN BANGGAI - Yusni, Yusni; Fitriani, Fitriani; Yadasang, Rosfianti M. (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to determine the level of effectiveness of the fixed asset management process at the BPKAD Office (Regional Asset Financial Management Agency) of Banggai Regency in accordance with the Minister of Home Affairs Regulation No. 19 of 2016, and what factors are obstacles in implementing the management of fixed assets of regional property at the BPKAD Office. The results of the study indicate that the level of effectiveness of the fixed asset management process at the BPKAD Office (Regional Asset Financial Management Agency) of Banggai Regency is not in accordance with the Minister of Home Affairs Regulation No. 19 of 2016, because of the 11 indicators of regional property management, only 9 cycles can be passed by the Banggai Regency Regional Asset and Financial Management Agency and the factors that are obstacles in implementing the management of fixed assets of regional property at the BPKAD Office (Regional Asset Financial Management Agency) of Banggai Regency, namely human resource factors and leadership factors.